APPEAL AS THE COURT OF SECOND INSTANCE, ITS ESSENCE AND SIGNIFICANCE - Karchaidze, Nato (European Scientific Journal, ESJ, 2012)
In early years, the civil procedural legislation considered only cassation rule of appeal against court adjudication. Nowadays, establishment of the appellant system is one of the most important results of the reform of the court system of our country. Theoretical investigation of the institute of appeal against court adjudications is of utmost importance to effectively raise realization of the right of court protection which is one of the most important constitutional rights of citizens.